PHP 8 programming tips, tricks and best practices : a practical guide offering insights into the new features and usage changes in PHP 8.X - Bierer, Doug; Evans, Cal (Packt Publishing, 2021)
Discover effective techniques, workarounds, and expert guidance for avoiding situations where your application might break following PHP 8 migration Key Features Get the hang of all the new features introduced in PHP 8 Learn how to detect potential code breaks and keep your application code running smoothly in PHP 8 Explore an exciting new trend - asynchronous PHP programming using Swoole and Fibers Book DescriptionThanks to its ease of use, PHP is a highly popular programming language used on over 78% of all web servers connected to the Internet. PHP 8 Programming Tips, Tricks, and Best Practices will help you to get up-to-speed with PHP 8 quickly. The book is intended for any PHP developer who wants to become familiar with the cool new features available in PHP 8, and covers areas where developers might experience backward compatibility issues with their existing code after a PHP 8 update. The book thoroughly explores best practices, and highlights ways in which PHP 8 enforces these practices in a much more rigorous fashion than its earlier versions. You'll start by exploring new PHP 8 features in the area of object-oriented programming (OOP), followed by enhancements at the procedural level. You'll then learn about potential backward compatible breaks and discover best practices for improving performance. The last chapter of the book gives you insights into PHP async, a revolutionary new way of programming, by providing detailed coverage and examples of asynchronous programming using the Swoole extension and Fibers. By the end of this PHP book, you'll not only have mastered the new features, but you'll also know exactly what to watch out for when migrating older PHP applications to PHP 8. What you will learn Gain a comprehensive understanding of the new PHP 8 object-oriented features Discover new PHP 8 procedural programming enhancements Understand improvements in error handling in PHP 8 Identify potential backward compatibility issues Avoid traps due to changes in PHP extensions Find out which features have been deprecated and/or removed in PHP 8 Become well-versed with programming best practices enforced by PHP 8 Who this book is for This book is for PHP developers at all levels who have experience in PHP 5 or above. If you're just getting started with PHP, you'll find the code examples useful for learning the language. Developers who have worked for a few months on one or more PHP projects will be able to apply the tips and techniques to the code at hand, while those with many years of PHP experience are sure to appreciate the concise coverage of new PHP 8 features.